Representation and Accuracy : An Examination of School Psychology Content in Introductory Psychology Textbooks - Judkins, Austin H. (East Carolina University, 2013)
The purpose of this study was to investigate the representation and accuracy of school psychology content in introductory psychology textbooks. A word count was conducted on each textbook to determine the number of words devoted to school psychology, as well as clinical, counseling, and I/O psychology. Average word count was calculated for each applied area. Then effect sizes were computed comparing school psychology to each applied area. Checklists designed to evaluate the accuracy of textbook descriptions were used to measure the accuracy of school psychology content. Using data from the checklist, a percentage was computed to represent the accuracy. The results indicated that school psychology was represented the least among applied areas, and the school psychology descriptions provided by the textbooks were overall limited. Those textbooks with the most representation and those that were most accurate are noted. Findings may be used to assist professors teaching introductory psychology courses in selecting a textbook that best covers the breadth of applied psychology fields, with an emphasis on school psychology because it is historically underrepresented in undergraduate texts relative to other applied areas of psychology.
Keywords: Psychology; Accuracy; Applied subfields in psychology; Introductory psychology course; Representation; School psychology; Textbooks; School psychology--Study and teaching--Textbooks; Psychology--Study and teaching--Textbooks